De-signing design cartographies of theory and practice - Grierson, Elizabeth; Edquist, Harriet 19XX-; Frichot, Hélène 1970-; Silverman, Hugh J. 1945-2013 (Textures: philosophy / literature / culture, 2015)
De-signing design: Cartographies of theory and practice' throws new light on the terrain between theory and practice in transdisciplinary discourses of design and art. The editors, Elizabeth Grierson, Harriet Edquist, and Helene Frichot, bring together diverse approaches to design theory, practice, and philosophy from leading scholars in Australia, New Zealand, Japan, and the United Kingdom. Themes include spatiality, difference, cultural aesthetics, and identity in the expanded field of place-making and being. The concept that design can be de-signed is presented as a way of exploring different approaches to an experimental and experiential thinking-doing that promises to further open up research possibilities in the fields of design and art thinking and practice. The book enacts a series of cartographic devices to articulate the spaces between theory and practice